Catholic Schools, Catholic Education, and Catholic Educational Research: A Conversation with Anthony Bryk - Bryk, Anthony (Catholic Education: A Journal of Inquiry and Practice, 2008)
Anthony Bryk is President of the Carnegie Foundation for the Advancement of Teaching. Previously, he held the Spencer Chair in Organizational Studies in the School of Education and the Graduate School of Business at Stanford University as well as the Marshall Field IV Professor of Urban Education and Sociology at the University of Chicago. Dr. Bryk received his undergraduate degree from Boston College and his doctorate from Harvard University. His main areas of expertise are school organization, education reform, Catholic schools, and educational statistics. He founded and directed efforts to support and inform educational improvements in the Chicago public schools. In 1993, Harvard University Press published the groundbreaking book Catholic Schools and the Common Good with Valerie Lee and Peter Holland. Dr. Bryk recently spoke with Joseph M. O’Keefe, S.J., dean of the Lynch School of Education at Boston College and co-editor of the journal, on the future of Catholic schools, Catholic educational research, and the journal. The following is a transcript of that conversation, providing direction for the future of Catholic education. [Special thanks to Craig Horning, doctoral student at Boston College, for transcribing the conversation.]